INFLUENCE RETURN ON EQUITY (ROE), RETURN ON ASSETS (ROA), EARNING PER SHARE (EPS), PRICE EARNING RATIO (PER) AND DEBT TO EQUITY RATIO (DER) SHARE PRICE OF AUTOMOTIVE AND COMPONENT COMPANIES LISTED ON INDONESIA STOCK EXCHANGE (IDX) IN 2010-2013 - Eka Wibowo Putro (Jurnal Ilmiah Mahasiswa FEB, 2015)
Maximizing the benefits for investor in an investment should be achieved by maximizing the value of the company. Company's value can be increased by enhancing the share price in the stock market which can be achieved by improving management performance. To measure the performance of the company, it may use financial ratios like Return on Equity (ROE), Return on Assets (ROA), Earning Per Share (EPS), Price Earnings Ratio (PER) and Debt to Equity Ratio (DER). This study aims to identify and analyze whether ROE, ROA, EPS, PER, and DER partially and simultaneously influence automotive and spare parts company's stock price listed in IDX during 2010-2013.This type of research is explanatory, which research that explains the position of the studied variables and the relationship between one variable and another variable. Total population in this study involve 12 companies. Sample selection is done by using purposive sampling method as the samples were selected based on certain criteria in order to obtain a representative sample . Based on the sample criteria, there are 12 companies observed in this research.These results indicate that ROE, ROA, EPS, PER, and DER simultaneously have a significant effect on stock prices. Yet, in partial analysis, the result shows that ROA and DER do not have any significant effect on stock prices, but not ROE, EPS and PER that have a significant effect on stock prices.Keywords : Stock Price, Return On Equity, Return On Assets, Earning Per Share, PriceEarnings Ratio, Debt to Equity Ratio.